Pengaruh Leverage, Pertumbuhan Penjualan, dan Ukuran Perusahaan terhadap Nilai Perusahaan Sub Sektor Perbankan di Bursa Efek Indonesia - Syahid Hidayat, Muhammad; Zulkarnain, Iskandar (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to examine the effect of leverage, sales growth, and firm size on firm value in the banking sub-sector listed on the Indonesia Stock Exchange (IDX) during the 2020-2024 period. A quantitative approach with panel data regression analysis was employed. Firm value was measured using Price to Book Value (PBV), leverage by Debt to Equity Ratio (DER), sales growth by Net Sales Growth Ratio, and firm size by the natural logarithm of total assets. The research sample consisted of 37 banking companies selected through a purposive sampling method. The results indicate that leverage has no significant effect on firm value. Conversely, sales growth has a positive and significant impact, while firm size negatively and significantly affects firm value. An adjusted R-squared value of 0.620348 suggests that 62.03% of the variation in firm value can be explained by this model, with the remainder attributed to other variables outside the model.